Effects of Homework Supported Distance Education on Academic Satisfaction, Academic Achievement, and Attitude towards Distance Education - Karabatak, Songul; Alanoglu, Muslim; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2020)
The purpose of this study is to reveal the effects of homework supported distance education on students' academic achievement, academic satisfaction, and attitudes towards distance education. This study was performed with a quantitative paradigm. In this context, repeated measures design was used. The purposeful sampling method was used to determine the participants. One-way analysis of variance (ANOVA) for repeated measures was used to compare academic achievement tests and scale scores. As a result of the study, the distance education process applied significantly increased students' academic achievement but supporting the distance education process with homework increased academic achievement more. The distance education process did not change the students' attitudes towards distance education and their academic satisfaction, but homework-supported distance education process changed positively. This finding revealed that distance education alone is not enough and it should be supported with different techniques and methods to increase its effectiveness. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: academic achievement; academic satisfaction; attitude towards distance education; Distance education; homework